Dinamika Sosial Remaja Pelaku Balap Liardi Kota Pekanbaru (Studi Pada Jalan Jenderal Sudirman, Pekanbaru) - Irlanda, Herru Nur; A, Askarial (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study explores the social dynamics of adolescents involved in illegal street racing in Pekanbaru City, specifically along Jenderal Sudirman street. The objective is to understand the process of youth involvement in street racing and examine the underlying social factors. Employing a qualitative approach with a case study method, data were collected through observation, interviews, and field documentation. The findings reveal that adolescent involvement in street racing occurs gradually, starting from peer influence and curiosity, eventually leading to active participation. This activity is driven not only by entertainment needs but also by the search for identity and social recognition. Street racing is conducted collectively and has formed a subculture with its own norms and symbols. Weak family control, lack of legal avenues for expression, and ineffective informal social control contribute to the persistence of this phenomenon. The impact is directly felt by local residents in the form of noise disturbances, fear, and economic losses. The study concludes that street racing reflects a complex social dynamic among adolescents, requiring an integrated approach involving families, communities, and government authorities.